Work Experience and Ability Boost Productivity in Indonesia While Burnout Remains Irrelevant: Pengalaman dan Kemampuan Kerja Meningkatkan Produktivitas di Indonesia, Sementara Burnout Tetap Tidak Relevan - Cahyani, Aditiya; Andriani, Dewi (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of work experience, ability, and burnout on productivity at PT Harapan Sejahtera Karya Utama. Using quantitative research with an associative approach, data was collected from 115 production employees via observation and Likert-scale questionnaires. Multiple linear regression analysis revealed that work experience and ability significantly enhance productivity, while burnout does not have a significant effect. The collective influence of these factors is also significant. These findings suggest that companies should focus on improving work experience and ability, and manage burnout to boost employee productivity. Highlight: Significant Factors: Work experience and ability positively impact employee productivity. Non-Significant Factor: Burnout does not significantly affect productivity. Collective Influence: Combined work experience, ability, and burnout significantly affect productivity. Keywoard: work experience, work ability, burnout, productivity, quantitative research